The modern agoras: the relationship between urban open public space and political expression. A case study of the city of Poznań, Poland - Wronkowski, Adam; Lorek, Artur (Bulletin of Geography. Socio-economic Series, 2024)
Contemporary urban public open spaces are stages of political expression, reminiscent of the historical Greek agoras that performed similar functions thousands of years ago. What has clearly changed, however, is the form of political expression. Rather than individual speeches by ancient thinkers and politicians, we are increasingly dealing with collective protests and assemblies presenting the views of the communities involved. Nowadays, public assemblies also take place in a much larger number of public spaces, depending on needs. They are chosen on the basis of three main categories of factors: spatial, semiotic and reception-related, which may overlap. The main objective of this paper is to determine the role of urban public open spaces as places of expression of political views during public assemblies. The study was based on the analysis of data from the Municipality of Poznań, as well as individual in-depth interviews with people involved in the organization of public assemblies in Poznań in 2019 and representatives of local associations.